Beyond Message Delivery: Embedded Dakwah as Islamic Value Formation and Managerial Reorientation - Maesaroh, Imas; Kholis, Nur; Hakim, Ahmad Khairul; Bramayudha, Airlangga; Zuhri, Syaifuddin; Labib, Mufti (Journal of Islamic Management, 2026)
This article develops the concept of embedded dakwah to explain how Islamic values are formed through everyday community life rather than only through verbal message delivery. Drawing on a narrative integrative review of dakwah studies, lived religion, social learning theory, ritual studies, community leadership, and religion–culture scholarship, the article identifies four domains of embedded dakwah: community leadership, everyday social interaction, collective religious practice, and local culture. It argues that Islamic value formation operates through four interrelated mechanisms: exemplary conduct, habituation, collective participation, and social norm reinforcement. The proposed framework is relational, contextual, and non-deterministic. Its formative effects depend on actor legitimacy, relational quality, power distribution, and community inclusivity. The article contributes to dakwah studies by shifting analytical attention from communication strategy and message transmission toward moral-social formation. It further develops an ecology-based organizational framework for dakwah institutions, covering leadership and governance, program design, the cultural and relational environment, and monitoring, as a practical guide for mosques, pesantren, and Islamic organizations seeking to cultivate Islamic values beyond event-based program delivery.